PROJECT-BASED LEARNING IN ENGLISH FOR SPECIFIC PURPOSES: ENHANCING STUDENTS’ SPEAKING SKILL THROUGH VIDEO TUTORIAL PROJECT - Kadek Yogi Susana; Ni Nyoman Ayu J. Sasthaparamitha (LPPM Universitas Dhyana Pura, 2019)
ABSTRACTThis article presents the results of the study on the impact of project-based learning onstudents’ speaking achievement particularly their presentation skills. The project-basedlearning was designed through several stages with video tutorial as its final product.Students were required to upload their video tutorial to their YouTube channel in order toinvite wider audience. Participants were 34 fourth-semester students enrolled in a fouryearundergraduate program in Informatics Engineering (Computer System). The goal ofthis project was to drive students’ engagement in speaking activities and enhance students’creativity in the context of English of Specific Purposes. This classroom action researchwas conducted in two cycles in which the quantitative data, i.e., three set of data including(pre-test and post-test1), (pre-test and post-test2) and (post-test1 and post-test2) wereanalyzed using SPSS statistic 21. The finding showed that the correlation coefficient (r) ofthe first data set was 0,902, the second data set was 0,712 and the third data set was 0,786.Based on the interpretation scale of correlation coefficient by Guilford (1965), the rangeof all the correlation coefficients implies that there is a strong relationship between beforeand after the treatment of PBL. Based on the result of analysis using SPSS statistics 21with 95% level of confidence, it was revealed that -tcount < -ttable (-12,085 < -2,01669, -16,352 <-2,01669 and -11,711<-2,01669) for all data set and the significance value of 2-tailed was less than 0,05 (0,000 < 0,05). It can be concluded that H1 was accepted and H0was rejected signifying that there was a significant effect of PBL implementation inimproving students’ speaking achievement. In other words, the results showed a significanteffect of PBL on students’ presentation skills in accordance with their backgroundknowledge in IT. Considering the positive result of this study, PBL is recommended to beapplied in teaching speaking for students in the context of English for Specific Purposesas it can improve students’ achievement.Keywords: Project-based learning, English for Specific Purposes, presentation skill,video tutorialABSTRAKArtikel ini menyajikan hasil studi tentang dampak pembelajaran berbasis proyek padaprestasi berbicara siswa terutama keterampilan presentasi mereka. Pembelajaranberbasis proyek dirancang melalui beberapa tahap dengan video tutorial sebagai produkakhirnya. Siswa diminta untuk mengunggah tutorial video mereka ke saluran YouTubemereka untuk mengundang audiens yang lebih luas. Partisipan adalah 34 mahasiswasemester empat yang terdaftar dalam program sarjana empat tahun di Teknik Informatika(Sistem Komputer). Tujuan dari proyek ini adalah untuk mendorong keterlibatan siswa Inggris untuk Tujuan Khusus. Penelitian tindakan kelas ini dilakukan dalam dua siklus dimana data kuantitatif, yaitu, tiga set data termasuk (pre-test dan post-test1), (pre-test danpost-test2) dan (post-test1 dan post-test2 ) dianalisis menggunakan statistik SPSS 21.Temuan menunjukkan bahwa koefisien korelasi (r) dari set data pertama adalah 0,902, setdata kedua adalah 0,712 dan set data ketiga adalah 0,786. Berdasarkan skala interpretasikoefisien korelasi oleh Guilford (1965), kisaran semua koefisien korelasi menyiratkanbahwa ada hubungan yang kuat antara sebelum dan sesudah pengobatan PBL.Berdasarkan hasil analisis menggunakan statistik SPSS 21 dengan tingkat kepercayaan95%, terungkap bahwa -hitung <-tabel (-12.085 <-2.01669, -16.352 <-2.01669 dan -11.711 <-2.01669 ) untuk semua set data dan nilai signifikansi 2-tailed kurang dari 0,05(0,000 <0,05). Dapat disimpulkan bahwa H1 diterima dan H0 ditolak menandakan bahwaada pengaruh yang signifikan dari implementasi PBL dalam meningkatkan prestasiberbicara siswa. Dengan kata lain, hasil menunjukkan efek signifikan PBL padaketerampilan presentasi siswa sesuai dengan latar belakang pengetahuan mereka dibidang TI. Mempertimbangkan hasil positif dari penelitian ini, PBL direkomendasikanuntuk diterapkan dalam pengajaran berbicara untuk siswa dalam konteks Bahasa Inggrisuntuk Tujuan Tertentu karena dapat meningkatkan prestasi siswa.Kata kunci: pembelajaran berbasis proyek, Bahasa Inggris untuk Tujuan Khusus,keterampilan presentasi, video tutorial